Entrepreneurship Profile of Students From two Peruvian Universities: a Comparative Study - Pezo-Arteaga, Erik (2024)
Introduction: The insertion into the labor market of university students is one of the most important motivations for pursuing higher education. At present, entrepreneurship is presented as an option that is becoming increasingly relevant. Objective. Identify and differentiate the way in which the entrepreneurship profile differs based on the population group to which the student belongs, influenced by sociodemographic factors. Methodology. Non-experimental, comparative-transversal, with a sample of 250 students from public and private universities, to whom a questionnaire of questions was administered to the students using the survey technique. To cross-reference the information and note the differences, we conducted a descriptive analysis using cross tables. To verify the hypotheses, the Mann-Whitney U and Kruskal-Wallis tests were used. Findings. It was identified that the only factor with significant value is the student’s work activity (0.027), while the other sociodemographic aspects presented a p-value > 0.05. Conclusion. There are no significant differences in the entrepreneurship profile in eight of the nine aspects evaluated. Implications. The entrepreneurship profile appears to be conditioned by the student’s current work activity.